The Interface between Human Rights and Terrorism: Towards Achieving an Effective Counter-Terrorism Regime (Dhaka University Law Journal, 2024)
Terrorism has become an emerging challenge to human rights protections today. Although terrorism has been present throughout modern history, international concern against it has become more visible since September 11, 2001. The international  community  has  adopted  various  instruments on counterterrorism, provisions of which have been incorporated into the domestic laws of different countries. These instruments representing the current counterterrorism regime prioritise national security over other issues including human rights. Therefore, while employing counterterrorism measures states often tend to promote their security at the expense of the lives, liberties, and properties of civilians. To protect the human rights of innocent people against such actions it is crucial to adopt an effective counterterrorism regime. This article explores how states could establish such a regime. It suggests that the proposed regime should be based on the human rights framework. The principles of necessity and proportionality will provide a useful guideline in this respect.Dhaka University Law Journal, Vol. 34(2), 2024 P. 1-23